2015
DOI: 10.1515/acve-2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation Of Sjenica Cheese With Regard To Coagulase-Positive Staphylococci And Antibiotic Resistance Of Lactic Acid Bacteria And Staphylococci

Abstract: Sjenica cheese is an artisanal cheese stored in brine, traditionally produced from raw sheep's milk in the southern part of Serbia -Sjenica Pester plateau.The aim of this study was to perform the safety evaluation of Sjenica cheese. As one of the safety criteria we considered the number of coagulase positive staphylococci and their enterotoxigenic potential. Antibiotic susceptibility/resistance patterns of autochthonous lactic acid bacteria and coagulase-positive staphylococci isolated from Sjenica cheese was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
2
1
0
Order By: Relevance
“…lactic acid bacteria. When examining Sjenica autochthonous cheese in brine in southwestern Serbia, produced from raw sheep's milk, during the monitored period of cheese production, the number of coagulase-positive staphylococci did not reach the value of 105 CFU/g (Bulajić et al, 2015), which coincides with the results of our study. Also, Zarate et al (1997) investigated Staphylococcus aureus in goat cheese from Tenerife (Spain), produced from raw milk, without the addition of starter, consumed fresh (within 2-3 days) or after ripening for 60 days.…”
Section: Results and Disscusionsupporting
confidence: 89%
“…lactic acid bacteria. When examining Sjenica autochthonous cheese in brine in southwestern Serbia, produced from raw sheep's milk, during the monitored period of cheese production, the number of coagulase-positive staphylococci did not reach the value of 105 CFU/g (Bulajić et al, 2015), which coincides with the results of our study. Also, Zarate et al (1997) investigated Staphylococcus aureus in goat cheese from Tenerife (Spain), produced from raw milk, without the addition of starter, consumed fresh (within 2-3 days) or after ripening for 60 days.…”
Section: Results and Disscusionsupporting
confidence: 89%
“…This work represents the first study of risk assessment of acid-set cheese related to CoPS in our region. Out of a total 50 samples, CoPS were isolated from 36 samples of cheese, or 72% of all samples, which is in compliance with the findings of other authors, who tested other sorts of traditional cheeses made from raw milk in our region (Bulaji c et al, 2015;Goli c et al, 2015). The European Commission (2005) suggested that raw milk products should not contain a high bacterial concentration (10 5 -10 6 CFU g À1 or mL À1 ), in order to prevent production of staphylococcal enterotoxins during the manufacturing process.…”
Section: Determination Of Cops Quantity In Acid-set Cheese Samplessupporting
confidence: 88%
“…and (10 of 13) 1601098 coagulase-positive cocci, notoriously carrying this determinant. In support of this hypothesis, tet(K) + strains ascribed to E. coli, Salmonella and S. aureus have recently been isolated from eggs intended for human consumption [34]; analogously, tet(K) + lactobacilli [35,36] and coagulase-positive staphylococci [36] have recently been isolated from different cheeses. With regards to this latter food matrix, a recent research aimed at identifying and detecting tetracycline and erythromycin resistance genes in Spanish and Italian retail cheeses revealed that traditional Italian cheeses might effectively act as a reservoir for many antibiotic resistance determinants, including tet(K) [37].…”
Section: Discussionmentioning
confidence: 99%